The impact of religious education in confronting violence, extremism, and terrorism in Islamic - Mohsen, Dr. Dunya Salman Mohsen (Sulaimani Journal for Humanities, 2026)
Religious education and awareness have a significant impact in reducing ideas of violence and terrorist extremism and treating them with awareness and awareness by clarifying the effects resulting from violence and extremism and the role of the Islamic religion in achieving psychological and physical security and peace and in addressing cases of ignorance that result from violence, extremism and terrorism. Ideas of violence, aggression and extremism are confronted and confronted by activating the role of religion in promoting awareness to avoid these extremist and aggressive ideas and strengthening religious, human and moral values through awareness of these values and demonstrating the importance of achieving peace and its impact on societal reality because the phenomenon of violence generated by intellectual extremism is one of the phenomena and diseases that threaten the security and stability of society. Religious discourse has a major role in ridding society of these scourges and intellectual diseases and explaining their consequences.
Keywords: violence and extremism in Islamic thought; the educational and religious impact on confronting violence Extremism and terrorism